2017
DOI: 10.1080/17588928.2017.1333490
|View full text |Cite
|
Sign up to set email alerts
|

Does spatial attention modulate the earliest component of the visual evoked potential?

Abstract: Whether visual spatial attention can modulate feedforward input to human primary visual cortex (V1) is debated. A prominent and long-standing hypothesis is that visual spatial attention can influence processing in V1, but only at delayed latencies suggesting a feedback-mediated mechanism and a lack of modulation during the initial afferent volley. The most promising challenge to this hypothesis comes from an event-related potential (ERP) study that showed an amplitude enhancement of the earliest visual ERP com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
68
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(93 citation statements)
references
References 61 publications
11
68
5
Order By: Relevance
“…Some studies challenged this view indicating the presence of attention effects on the C1 component (Kelly, Gomez‐Ramirez, & Foxe, ; Rauss et al, 2009), although this result was never further confirmed. More importantly, a recent study that carefully replicated the same experiment and analysis strategies as in Kelly et al () found no evidence for an attention‐based modulation of the C1 (Baumgartner et al, ). Furthermore, normal and reliable chromatic VEPs have been recorded in cases of cerebral achromatopsia.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Some studies challenged this view indicating the presence of attention effects on the C1 component (Kelly, Gomez‐Ramirez, & Foxe, ; Rauss et al, 2009), although this result was never further confirmed. More importantly, a recent study that carefully replicated the same experiment and analysis strategies as in Kelly et al () found no evidence for an attention‐based modulation of the C1 (Baumgartner et al, ). Furthermore, normal and reliable chromatic VEPs have been recorded in cases of cerebral achromatopsia.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, for several studies the presence of VEPs activity over the occipital cortex along the midline, was sufficient to indicate that the signals come from V1 (Foxe et al, ; Kulikowski et al, ; Nakamura et al, ; Onofrj et al, ; Xing et al, ). Highsmith and Crognale () proposed that early chromatic VEP should arise from V1 because of the lack of attention effect on the C1 component (e.g., Baumgartner et al, ; Di Russo et al, ; for a review see Ding, Martinez, Qu, & Hillyard, ). Some studies challenged this view indicating the presence of attention effects on the C1 component (Kelly, Gomez‐Ramirez, & Foxe, ; Rauss et al, 2009), although this result was never further confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ERP studies, usually focusing on poststimulus brain activity, showed that visuospatial attention enhances activities originating in dorsal and ventral extrastriate pathways, indexed by the P1 and the N1 components. Furthermore, visuospatial attention does not affect the afferent activities originating in the primary visual area (V1), indexed by the C1 component (Baumgartner, Graulty, Hillyard, & Pitts, ; Di Russo, ; Gómez‐Gonzalez, Clark, Fan, Luck, & Hillyard, ; Pitts & Hillyard, ; however, see Slotnick, for opposite results). Regarding attention effects on frontal areas, ERP evidence is scarce.…”
Section: Introductionmentioning
confidence: 99%